Discharge and flow characteristics using magnetic fluid spikes for air pollution control. (16th June 2015) - Uehara, S; Itoga, T; Nishiyama, H
Abstract: This paper presents an investigation of the atmospheric discharge and flow characteristics using a magnetic fluid (MF) for an air cleaning device. High-voltage ac is applied between MF spikes formed under a magnetic field and a flat-plate electrode. These MF-spikes are stretched upward to the opposing electrode sharpening its tip until discharge is generated. Furthermore, MF droplets are ejected from the tips of the spikes (a phenomenon known as electrospray) depending on the MF properties and operating conditions. The atmospheric discharge characteristics were investigated by measuring the discharge current. The cleaning ability of the system was evaluated by measuring the produced ozone concentrations.